A high-resolution 20K SNP array for comprehensive genotyping and genetic mapping in Nicotiana tabacum L. - Shizhou Yu; Zhixiao Yang; Jie Zhang; Linggai Cao; Jie Liu; Peng Lu; Jiemeng Tao; Jufen Wan; Qingdong Zeng; Tenghang Xu; Peijian Cao; Jingjing Jin; et al. (Crop Journal)
Nicotiana tabacum (2n = 4x = 48), an economically important non-food crop and a model plant for genetic studies, faces challenges in efficient genotyping of novel germplasm. To address this, we developed the Ta-LD-SC, a 20K SNP Affymetrix Axiom array, based on resequencing data from 150 tobacco accessions. A total of 20,213 unique SNPs were carefully selected, achieving coverage of over 90% of the tobacco genome (Nitab4.5 and NtaSR1) with a uniform probe distribution, limiting density to no more than 5 SNPs per 200 kb. The array underwent extensive validation using 866 tobacco accessions (NP panel) and 288 F2 individuals from a cross between K326 and Oxford 26 (GP panel). Performance metrics demonstrated its robustness, with high SNP call rates (93.6%–99.8%), a low technical error rate (< 1%), and a superior PolyHighResolution SNP rate (79.79%) compared to other crop SNP arrays. Population structure analysis of the NP panel revealed two major introductions of foreign germplasm that have significantly influenced the genetic diversity of Chinese tobacco resources. Using the array, a genome-wide association study (GWAS) identified 62 genes linked to eight agronomic traits, and a high-density genetic map encompassing 4553 SNPs across 6606.08 cM was constructed. The Ta-LD-SC array provides a valuable tool for rapid, high-quality genotyping offering supporting marker annotations that may benefit genetic research and breeding of tobacco.